INVESTIGATION OF SEICHES AND SEICHELIKE OSCILLATIONS IN THE MODEL BASIN, APPROXMATING THE LADOGA LAKE - Yury Manilyuk; Leonid Cherkesov (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2017)
Seiches (single-period) and seiche-like oscillations (superposition of different seiche modes) were studied in a constant-depth rectangular model tank with dimensions characteristic ofLakeLadoga using the results of analytical solution of a system of long wave equations. The periods of the first fourteen seiche modes were calculated. The following values were found: 5.22; 2.61; 2.09; 1.94; 1.74; 1.63; 1.34; 1.30; 1.11; 1.04; 1.02; 0.97; 0.93 hours. The possible flow velocities were estimated. It is found that where the level oscillations amplitude was within25 cm, wave flow velocity did not exceed 11 cm/s for all the considered seiche modes. The spatial structure of level oscillations and characteristics of wave currents was analyzed. A classification of seiches has been produced. It is found that the formation of a variety of seiche-like oscillation systems is possible inLakeLadoga. These systems represent a superposition of several seiche modes. Their properties are determined by a set of interacting modes. Level oscillations in this case are not periodic and differ substantially from oscillations in the case of a single seiche. Three types of seiche-like oscillations have been distinguished. The first one corresponds to an interaction of longitudinal and transverse seiches. Nodal lines of the level are rotated over time, and the rotation direction changes periodically. The second type corresponds to an interaction or either longitudinal or transverse seiches with different periods. In this case, the number of nodal lines may change over time. They move parallel to a coordinate axis. Angles between these lines and coordinate axes are constant. The third type corresponds to an interaction of a longitudinal and a transverse seiches with equal periods. The position of nodal lines did not change with time. Maximum level elevations of seiche-like oscillations are close to the sum of the amplitudes of the interacting waves. The greatest magnitudes of wave current velocity were in all cases lower than the sum of flow velocities of the interacting modes. The goodness of fit of the calculated results to field data was quite satisfactory.